2020
DOI: 10.2217/epi-2019-0153
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Expression Profile and m6A Modification Analysis in Poorly Differentiated Adenocarcinoma of the Stomach

Abstract: Aims: To profile and characterize the circular RNA (circRNA) expression pattern in poorly differentiated gastric adenocarcinoma (PDGA). Methods & materials: CircRNA expression profiles in PDGA and adjacent nontumor tissues were analyzed by microarray. Five randomly selected differentiated expressed circRNAs (DECs) were validated by real-time quantitative PCR. m6A qualification of the top 20 DECs was conducted by m6A-immunoprecipitation and real-time quantitative PCR. Results: A total of 65 DECs were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…30 upregulated circRNAs and 35 downregulated circRNAs were evaluated in poorly differentiated gastric adenocarcinoma (PDGA) by circRNA microarray. The level of m 6 A was positive relative with circRNA in PDGA, which indicated that m 6 A-modified circRNA plays a role in GC progression 130 .…”
Section: A-modified Circrna Associated With Pathophysiological Processesmentioning
confidence: 85%
See 1 more Smart Citation
“…30 upregulated circRNAs and 35 downregulated circRNAs were evaluated in poorly differentiated gastric adenocarcinoma (PDGA) by circRNA microarray. The level of m 6 A was positive relative with circRNA in PDGA, which indicated that m 6 A-modified circRNA plays a role in GC progression 130 .…”
Section: A-modified Circrna Associated With Pathophysiological Processesmentioning
confidence: 85%
“…Cancer is a leading cause of mortality worldwide 137 . Based on the structure and function of m 6 A-modified circRNA, researchers have found that they play an important role in the progression, proliferation and metastasis of cancers, such as colorectal cancer 128 , gastric cancer 129 , hepatocellular carcinoma (HCC) 130 , 131 and poorly differentiated gastric adenocarcinoma 132 .…”
Section: A-modified Circrna Associated With Pathophysiological Processesmentioning
confidence: 99%
“…Chen et al identified that circNSUN2 could form a circNSUN2/IGF2BP2/ HMGA2 RNA-protein ternary complex to enhance the stability of HMGA2 mRNA in colorectal carcinoma [85]. Microarray analysis of DECs in poorly differentiated gastric adenocarcinoma revealed that most DECs had m 6 A modification, and the trend of m 6 A modification changes was consistent with the expression level of circRNAs [86]. Circ_0001105 suppressed the progression of osteosarcoma through sponging miR-766 to enhance the expression of YTHDF2 [87].…”
Section: Function Of Circrnas In Ferroptosismentioning
confidence: 90%
“…The present review elucidates the effects exerted by ncRNA modifications in carcinoma pathogenic mechanisms, as shown in Table1 . 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 …”
Section: Epigenetic Consequences Of Ncrna Modificationsmentioning
confidence: 99%
“…By microarray analysis, Zhang et al. 89 analyzed circRNA expression profiles in adjacent nontumor tissues and poorly differentiated gastric adenocarcinoma (PDGA). Five randomly selected differentially expressed circRNAs (DECs) were verified by quantitative real-time PCR.…”
Section: Epigenetic Consequences Of Ncrna Modificationsmentioning
confidence: 99%